SOSIALISASI DAN PELATIHAN PENGOLAHAN LIMBAH KULIT SINGKONG SEBAGAI PAKAN TERNAK KERBAU DI KABUPATEN MALUKU BARAT DAYA - Harmoko Harmoko; J. M. Samputty; J. Makatita; A. Sairudy; R. Dolewikou; B. Gairtua (Batara Wisnu : Indonesian Journal of Community Services, 2021)
The availability of feed in the livestock business is one of the determining factors for the success of feed because, with the presence of feed, farmers can design or measure the achievement of the livestock business targets carried out. Conducting socialization and training on processing cassava peel waste into animal feed can be a solution for buffalo farmers in Southwest Maluku Regency if they experience a shortage of feed availability, especially during the dry season. This socialization and training were carried out in Werwaru Village, Moa Island, Southwest Maluku Regency. Implementing socialization and training involves conducting lectures (exposure to the material), question and answer sessions, and training sessions on processing cassava peel waste. This activity was attended by 29 farmers, two village officials, 15 students, and four lecturers from the livestock study program so that the total participants who attended the PKM activity were 50 people. The socialization and training activities results showed that farmers in Werwaru village felt so helped by this training activity because it could increase their knowledge about the source of animal feed, while the processed cassava peel waste showed better results and could be used as a source of feed for livestock